Challenges and principles in teaching semantic web technologies. (9th February 2009) - Antoniou, Grigoris; Doerr, Martin
The semantic web is a recent initiative of great significance and with the promise to enrich the current state of the WWW. Teaching of the basic semantic web techniques poses new challenges. This paper discusses the challenges, and studies two ideas: a project centred approach, and the use of conceptual modelling as a multidisciplinary approach.